2006
DOI: 10.1111/j.0008-3658.2006.00134.x
|View full text |Cite
|
Sign up to set email alerts
|

Frontier engineering: from the globe to the body in the Cold War Arctic

Abstract: The dual themes of sovereignty and wilderness have come to define, or at least dominate, historical discussions of the North American Arctic. This paper argues that neither adequately captures the role of the Arctic during the early Cold War, a period of unprecedented interest in northern landscapes. Political and environmental approaches, with their national undertones, were incorporated into a dominant narrative whose implications were far less abstract: the Arctic became a frontier for military science, bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 51 publications
(52 reference statements)
0
27
0
3
Order By: Relevance
“…70 The Army Signals Corps was working on the use of altimeters over ice, while the Quartermaster Corps was using Antarctica to test equipment and clothing for use in the 67 Arctic -one of the frontlines in the Cold War. 71 In turn, the US Navy and TRAG were present in a supporting role; responsible for moving scientists and equipment both to and across the continent; although the Navy also carried out their own research into oceanography from their icebreakers. 72 Indeed, the US Navy's involvement in Antarctic affairs went back some years, to the work of Admiral Richard Byrd, via the United States Navy Antarctic Development Program, 1946-47, or Operation Highjump.…”
Section: Geophysics Geopolitics and The Military During And After Thmentioning
confidence: 99%
“…70 The Army Signals Corps was working on the use of altimeters over ice, while the Quartermaster Corps was using Antarctica to test equipment and clothing for use in the 67 Arctic -one of the frontlines in the Cold War. 71 In turn, the US Navy and TRAG were present in a supporting role; responsible for moving scientists and equipment both to and across the continent; although the Navy also carried out their own research into oceanography from their icebreakers. 72 Indeed, the US Navy's involvement in Antarctic affairs went back some years, to the work of Admiral Richard Byrd, via the United States Navy Antarctic Development Program, 1946-47, or Operation Highjump.…”
Section: Geophysics Geopolitics and The Military During And After Thmentioning
confidence: 99%
“…In bringing military artistic and scientific knowledges into close correspondence, the camoufleurs showed that camouflage brings the background to the fore as a dynamic and decisive element to survival, to life. Therefore, where the history of the military-industrial-complex has been well examined (Barnes, 2006;Farish, 2006;Pickering, 1995), this paper considers the military-scientific-artistic-complex that the military also demanded in WWII. Camouflage necessitates a deep understanding of our environment, our placing in world, and on the world.…”
Section: Resultsmentioning
confidence: 99%
“…As Farish ( ) highlights in his work on the Arctic, the geopolitical rivalry and instability of the Cold War provided a backdrop against which militaries would be pitted against the earth's most hostile environments. Indeed, the US military were enthusiastically studying and engaging with extreme environments and terrains after the onset of the Cold War and increasingly configuring the world ‘as a patchwork of hostile environments’ to be mastered (Farish , 193).…”
Section: Dwelling In Cold War Geopoliticsmentioning
confidence: 99%